Effect of carbon equivalent on thermal and mechanical properties of compacted graphite cast iron. Issue 16 (1st August 2016) - Liu, Yangzhen; Xing, Jiandong; Li, Yefei; Wang, Yong; Wang, Lei; Zheng, Baochao; Tao, Dong
Abstract: Abstract : The effects of carbon equivalent on thermal and mechanical properties of compacted graphite cast irons were investigated at ambient temperature, 300 and 500 °C, respectively. The group implied the change of carbon content to control the carbon equivalent. The results indicated that with the increasing carbon equivalent from 4.43 to 4.74, the graphite count increase. The thermal conductivity was 48.64, 44.55, 49.04, and 50.36 W/mK for carbon equivalent about 4.43–4.74 of compacted graphite cast irons at ambient temperature, respectively. With an increase in temperature, the thermal conductivity decrease. Moreover, with the increasing carbon equivalent, the tensile strength and yield strength increase initially, and then decrease at ambient temperature, 300 and 500 °C, respectively. With an increase in temperature, the tensile strength and yield strength decrease. Characterization of fracture surface indicated that the mixed ductile-brittle fracture mode prevailed in the compacted graphite cast irons with different carbon equivalents.